2012
DOI: 10.1038/gim.2011.56
|View full text |Cite
|
Sign up to set email alerts
|

Cost savings through molecular diagnosis for hereditary hemorrhagic telangiectasia

Abstract: Purpose: Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disorder of vascular development resulting in direct connections between the arterial and venous systems, bypassing capillaries. Symptoms and signs can appear throughout life and marked intrafamilial variability confounds diagnosis based purely on clinical criteria. We set out to determine the impact of genetic testing on the cost of screening for HHT in at-risk relatives. methods:We performed economic modeling of idealized pedigrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…To see more patients and to perform additional academic activities such as research and teaching, medical geneticists often choose to work overtime, and many continue to work evenings and weekends at home. 10 This situation may account for some of the frustration regarding the working conditions of professionals practicing medical genetics in this era, as was raised by the comments received in this study. The gap between the complexity and effort required for those working in medical genetics and the lack of proper appraisal of individuals and institutes providing genetic services is bound to have a negative effect on the attractiveness of this profession to those considering entering the field.…”
Section: Discussionmentioning
confidence: 88%
“…To see more patients and to perform additional academic activities such as research and teaching, medical geneticists often choose to work overtime, and many continue to work evenings and weekends at home. 10 This situation may account for some of the frustration regarding the working conditions of professionals practicing medical genetics in this era, as was raised by the comments received in this study. The gap between the complexity and effort required for those working in medical genetics and the lack of proper appraisal of individuals and institutes providing genetic services is bound to have a negative effect on the attractiveness of this profession to those considering entering the field.…”
Section: Discussionmentioning
confidence: 88%
“…Such cascade testing of relatives can allow diagnosis in an entire family, followed by recommended screening and management. 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…HHT presents a high and age-dependent penetrance, so once an index case is diagnosed within the family, the molecular genetic analysis of ENG, ACVRL1, SMAD4, and GDF2 can be used as a very predictive molecular diagnosis of the other at risk family members. Of note, some studies have found that a strategy of diagnostic genetic testing provides a more economically advantageous solution than the conventional clinical screening, because it reduces the number of clinical tests for those family members who do not have HHT [15].…”
Section: Introductionmentioning
confidence: 99%